Crisis spreading in multinational firms’ network: the dual influence of local interactions - Tsouchnika, Maria; Kanetidis, Michael; Argyrakis, Panos; Rozenblat, Celine (Frontiers in Complex Systems, 2023)
This study investigates the characteristics of multinational firm's interactions within and across activity sectors and the impact of intra-urban connections, during crisis propagation. By employing data that reflect ownership relations aggregated on the city level, we constructed the partialmultiplex, directed network of cities, divided into five layers by activity sector. The network was examined in two states: one excluding intra-urban interactions and one including them. The difference between these two states highlight the significant role of intra-urban networking processes in the global economy. The five layers differ both structurally and in terms of vulnerability during crisis propagation. The Knowledge Intensive Service (KIS) layer is the densest and most populous layer of all and its firms are more likely to be owners than subsidiaries. Using a simple stochastic Susceptible-Infected-Recovered (SIR) model, we simulated a crisis diffusion on the network of cities. Our results revealed that in the absence of intra-urban connections, KIS was both the most vulnerable and most influential layer in crisis propagation. The inclusion of intra-urban links sets off a complex interplay of factors that affect diffusion outcomes in nuanced ways: while it generally enhances the impact of the crisis and the influence across layers becomes rather homogeneous it can also have a protective effect, in cases of very dense and well-connected layers, such as KIS.